Analisis Keberlanjutan Agribisnis Paprika di Kabupaten Gowa (Studi Kasus Kelompok Tani Veteran Buluballea Malino) - Arham Haryadi; Baharuddin Patandjengi; Nurdjanah Hamid (Jurnal Sosial Ekonomi Pertanian, 2022)
The research was aimed to (1) identify the level of sustainability of the paprika agribusiness in Gowa Regency, (2) identify the factors affecting the sustainability of the paprika agribusiness in Gowa Regency. Rap-Paprika's MDS (Multidimensional Scaling) analysis is used to identify the level of sustainability as well as factors affecting the sustainability of paprika agribusiness in Gowa Regency in terms of economic, ecological, social, technological and institutional dimensions. The results of this study show that the level of sustainability of agribusiness peppers in Gowa Regency is at a sustainable level with an index value of 72.83. This result shows that the agribusiness of peppers in Gowa Regency is already running quite well, where the very sustainable dimension is shown the social dimension, while the economic dimension, ecological dimension, technological dimension, and institutional dimension still need attention from policymakers, so that the sustainability of these four dimensions can be raised to a very sustainable level. From the results of the MDS analysis of 5 dimensions of sustainability and 49 sustainability attributes, showing 15 sensitive attributes that show the most dominant factor affecting the sustainability of paprika agribusiness in Gowa Regency, Monte Carlo and MDS analysis showed that the value of the status of the paprika sustainability index in Gowa Regency in each dimension with a confidence interval of 95%, the MDS analysis results showed S-Stress values for all dimensions and multidimensional had a smaller value from 0.25, the coefficient of determinatinon (R²) value of each dimension and multidimensional is close to the values 1. These results show that the interrelationship of all attributes used in each dimension in the Rap-paprika MDS analysis is good enough to untangle the problem of agribusiness sustainability of peppers in Gowa Regency.